Discovery of an unusually compact lensed Lyman-break galaxy from the Hyper Suprime-Cam Survey. Issue 3 (28th February 2020) - Jaelani, Anton T; More, Anupreeta; Sonnenfeld, Alessandro; Oguri, Masamune; Rusu, Cristian E; Wong, Kenneth C; Chan, James H H; Suyu, Sherry H; Kayo, Issha; Lee, Chien-Hsiu; Inoue, Kaiki T
ABSTRACT: We report the serendipitous discovery of HSC J0904–0102, a quadruply lensed Lyman-break galaxy (LBG) in the Survey of Gravitationally-lensed Objects in Hyper Suprime-Cam Imaging (SuGOHI). Owing to its point-like appearance, the source was thought to be a lensed active galactic nucleus. We obtained follow-up spectroscopic data with the Gemini Multi-Object Spectrographs on the Gemini South Telescope, which confirmed this to be a lens system. The deflecting foreground galaxy is a typical early-type galaxy at a high redshift of z_=0.957 with stellar velocity dispersion σ_v=259±56 km s −1 . The lensed source is identified as an LBG at z_s=3.403, based on the sharp drop bluewards of Ly α and other absorption features. A simple lens mass model for the system, assuming a singular isothermal ellipsoid, yields an Einstein radius of θ_Ein=1.23 arcsec and a total mass within the Einstein radius of M_Ein=(5.55±0.24)×10^11M_ corresponding to a velocity dispersion of σ_SIE=283±3 km s −1, which is in good agreement with the value derived spectroscopically. The most isolated lensed LBG image has a magnification of 6.5 . In comparison with other lensed LBGs and typical z4 LBG populations, HSC J0904–0102 is unusually compact, an outlier at >2σ confidence. Together with a previously discovered SuGOHI lens, HSC J1152+0047, which is similarly compact, we believe that the HSC survey is extending LBG studies down to smaller galaxy sizes.